Online identities in and around organizations: A critical exploration and way forward. (January 2023) - Barros, Marcos; Alcadipani, Rafael; Coupland, Christine; Brown, Andrew D
The construction, performance, and regulation of identities in the online world have deep implications for individuals, organizations, and society, particularly as digital technologies become increasingly omnipresent in our daily lives. In the last decades, analyses of online identities' processes have moved from the exploration of identity play, through identity performance, toward a growing identity regulation through algorithmic management and the monetization of personal data. Despite a significant tradition of critical management and organization studies literature on identity, online identities have to date received only scant attention. This Special Issue explores what critical management and organization studies can contribute to research on online identities. Drawing on empirical analysis of virtual forums, social media, and platforms, the six papers included here highlight the struggles that accompany identity processes in the online environment and their implications for workers, activists, and other organized selves. In this introduction, we contextualize these contributions with reference to online identities studies and metaphors of the internet as a place, a tool, and a way of being. We comment on the contributions they make relating to the role of the body, and individual and collective dynamics in online identities processes. Following this, we propose critical ways forward concerning new forms of digital work, multiphrenic context collapse, and online references and sources of identity. We invite researchers to not only critically explore but also to engage with this brave new world that increasingly shapes our individual and collective selves.